Risk Analysis of Management and Mitigation in Msmes: Roti Maryam Dinoyo Branch - Chamila, Mulida Noer; Hikmah, Kholis Mufaidatul; Bastomi, Mohamad; Idris, Ahmad (Universitas Islam Kadiri, 2025)
Introduction/Main Objectives: Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in the Indonesian economy. However, MSMEs often face risk challenges that interfere with business continuity. Background Problems: One of the MSMEs that faces these challenges is Roti Maryam Dinoyo Branch which experiences internal risks such as machine damage, decreased quality of raw materials, and human resource and system risks. Novelty: This study highlights a holistic risk management approach in micro-scale MSMEs with specific case studies, offering risk mapping based on impact and probability, which is rarely done in MSMEs in the small food sector. Research Methods: This research uses a qualitative approach through observation and interviews with business actors. Data is reviewed to identify, evaluate, and mitigate the risks faced. Finding/Results: The results showed that the highest risk lies in running out of raw materials (red zones), while the intermediate risks include fluctuations in demand, decreased jam quality, and dependence on owners. Low risk is found in engine failure. Mitigation strategies include buffer stock, HR training, routine machine maintenance, and automated ordering systems. Conclusion: The implementation of effective risk management can improve operational efficiency and business sustainability, as well as reduce the negative impact of uncertainty. Risk evaluation is an important basis for decision-making and strategy formulation. Research limitation/implications: This study is limited to one MSME in one location and uses qualitative methods, so the generalization of results is still limited and requires a broader study on MSMEs in other sectors and regions for higher validity.